Study of neutron generation in the compact tokamak TUMAN-3M in support of a tokamak-based fusion neutron source. (11th September 2017) - Kornev, V.A.; Askinazi, L.G.; Belokurov, A.A.; Chernyshev, F.V.; Lebedev, S.V.; Melnik, A.D.; Shabelsky, A.A.; Tukachinsky, A.S.; Zhubr, N.A.
Abstract: The paper presents DD neutron flux measurements in neutron beam injection (NBI) experiments aimed at the optimization of target plasma and heating beam parameters to achieve maximum neutron flux in the TUMAN-3M compact tokamak. Two ion sources of different design were used, which allowed the separation of the beam's energy and power influence on the neutron rate. Using the database of experiments performed with the two ion sources, an empirical scaling was derived describing the neutron rate dependence on the target plasma and heating beam parameters. Numerical modeling of the neutron rate in the NBI experiments performed using the ASTRA transport code showed good agreement with the scaling.